Efficacy, safety, and predictors of response to infliximab therapy for ulcerative colitis: A Korean multicenter retrospective study. Issue 12 (December 2013) - Lee, Kang‐Moon; Jeen, Yoon Tae; Cho, Ju Yeon; Lee, Chang Kyun; Koo, Ja‐Seol; Park, Dong Il; Im, Jong Pil; Park, Soo Jung; Kim, You Sun; Kim, Tae Oh; Lee, Suck‐Ho; Jang, Byung Ik; et al.
Abstract Background/Aims Infliximab is currently used for the treatment of moderate‐to‐severe ulcerative colitis (UC) with an inadequate response to conventional agents. The efficacy and safety of infliximab in Korean patients with UC were assessed. Methods This was a retrospective multicenter study including all adult patients who received at least one infliximab infusion for UC. Short‐ and long‐term clinical outcomes and adverse events of infliximab therapy were evaluated, and predictors of response were identified. Results A total of 134 UC patients were included. The indications for infliximab therapy were acute severe UC in 28%, steroid‐dependency in 38%, and steroid‐refractoriness in 33%, respectively. The rates of clinical response and remission were 87% and 45% at week 8. In multivariate analysis, we found significant predictors of clinical remission at week 8: immunomodulator‐naïve (odds ratio [OR] = 4.89, 95% confidence interval [CI]: 1.44–16.66, P = 0.01), hemoglobin ≥ 11.5 g/dL (OR = 4.47, 95% CI: 1.48–13.45, P = 0.008), C‐reactive protein ≥ 3 mg/dL (OR = 4.77, 95% CI: 1.43–15.94, P = 0.01), and response at week 2 (OR = 20.54, 95% CI: 2.40–175.71, P = 0.006). Long‐term clinical response and remission rates were 71% and 52%, respectively, and mucosal healing was the only factor influencing long‐term response. Adverse events related to infliximab occurred in 15% of patients, and most of them were mild and transient. Conclusions Infliximab is effective and safe in the treatment of active UC in Korea. No history of previous immunomodulator use and high baseline C‐reactive protein are independent predictors of good response.